2019
DOI: 10.3390/polym11030484
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Various Ceramic Fillers on Thermally Conductive Polyimide Composite Films and Their Model Predictions

Abstract: In this study, thermally conductive composite films were fabricated using an anisotropic boron nitride (BN) and hybrid filler system mixed with spherical aluminum nitride (AlN) or aluminum oxide (Al2O3) particles in a polyimide matrix. The hybrid system yielded a decrease in the through-plane thermal conductivity, however an increase in the in-plane thermal conductivity of the BN composite, resulting from the horizontal alignment and anisotropy of BN. The behavior of the in-plane thermal conductivity was theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Moreover, a TC of 2.23 W/(m•K) was achieved when SiC whisker and AlN were co-added at a volume ratio of 25 : 75 to make up 50 vol% of the total ller content. Moreover, coadditions of AlN and hBN have been carried out by Kume et al (2009), Song et al (2019), andLiu et al (2020).…”
Section: Recent Research For Thermal Conductivity Of Pi-based Compositesmentioning
confidence: 99%
“…Moreover, a TC of 2.23 W/(m•K) was achieved when SiC whisker and AlN were co-added at a volume ratio of 25 : 75 to make up 50 vol% of the total ller content. Moreover, coadditions of AlN and hBN have been carried out by Kume et al (2009), Song et al (2019), andLiu et al (2020).…”
Section: Recent Research For Thermal Conductivity Of Pi-based Compositesmentioning
confidence: 99%
“…In the practical application, considering the economy and process simplicity, the >30 wt% micro-sized BN, 41,42 Al 2 O 3 (ref. 31) and AlN 31 were commonly introduced to the PI matrix to achieve an increase of 1000% in the thermal conductivity, while also meeting a practical requirement of heat management. 43 By comparison, the 35 wt% Al 2 O 3 @BN&BN/PI composite lm containing 17 wt% BN and 18 wt% Al 2 O 3 achieved the thermal conductivity of 3.35 W m À1 K À1 and a relatively high enhancement of 1664%.…”
Section: Thermal Conductivity Of Pi Composite Lmsmentioning
confidence: 99%
“…The as-prepared Al 2 O 3 @PI thin lm was obtained with an effective thermally conductive network, and also has good thermal and mechanical properties. Song et al 31 found that anisotropic BN and spherical Al 2 O 3 or aluminum nitride (AlN) formed a synergistic thermally conductive network structure, thus improving the thermal conductivity of the composite lm. Due to its good insulation performance and high thermal conductivity of up to 600 W m À1 K À1 , BN has been well known as a relatively ideal ller for the preparation of composites with high thermal conductivity and electrical insulation.…”
Section: Introductionmentioning
confidence: 99%
“…The Maxwell, Hashin-Shtrikman, and Lewis-Nielsen models were used in the theoretical calculations. The Maxwell model is limited to single filler component and hence more than one filler was used in this study, and Lewis-Nielsen model is used [31]. However, the most frequently used model in the literature for 3-phase systems is modified Lewis-Nielsen approach.…”
Section: Thermal Conductivity λmentioning
confidence: 99%